Application of yuba films for preserving beef patties. (September 2020) - Kim, Woojeong; Ryu, Jee-Hoon; Kim, Yookyung
Abstract: This study focused on yuba films coated with active agents to improve microbiological and oxidative stability and the feasibility of preserving beef patties. Yuba films (YC) coated with oregano essential oil (YO), grapefruit seed extract (YG), and their mixture (YOG) were characterized and applied to beef patties. YO (2.56 × 10 − 10 g m/Pa·sec· m 2 ) displayed exceptional water barrier properties compared to YC (4.27 × 10 − 10 g m/Pa·sec· m 2 ) . All coated yuba films showed increased antioxidant capacity, particularly YG. In disc diffusion, all coated yuba films (inhibition zones ≥ 20.0 mm) were strongly effective against L. monocytogenes, whereas YO (27.17 mm) and YOG (29.00 mm) were effective against E. coli O157:H7. In the application to beef patties, YG beef patties (1.69 MDA mg/kg) showed the highest oxidative stability as a result of lipid oxidation inhibition (YC 1.88 MDA mg/kg). Furthermore, YG beef patties maintained the highest quality of meat color, which was dark purplish-red, during storage. While E. coli O157:H7 in beef patties was significantly inhibited by YO and YOG, the growth of L. monocytogenes in beef patties was impeded by all coated yuba films throughout the storage period. Overall, YOG can be potentially used to increase microbiological safety and extend the shelf life of beef patties. Highlights: Yuba is a protein-lipid film formed at the surface of soymilk during heating. Yuba was coated with oregano essential oil (OR) and grapefruit seed extract (GSE). OR-coated yuba had a strong water barrier and antimicrobial activity. GSE-coated yuba contributed the most to preserving the color of the beef patties. Yuba coated with OR and GSE could be employed as a wrap for beef patties.